European Handball Federation information. EHF youth coaches' course (1999)
Course documentation of the 1999 EHF youth coaches' course in Rothenburg a.d. Fulda / Germany. The main contents are: - Introduction / Welcome - Long-term Performance Improvememt in Youth Training - Experts' Opinions - Young Goalkeepers' Training / Defence Training - A Focus on Action Speed Training - Individual Attack Behaviour / Training the Fast Break - Key Note Address / Closing